Prevention of Experimental Postoperative Peritoneal Adhesions through the Intraperitoneal Administration of Tanshinone IIA - Wang, Chengxi; Li, Xiao; Meng, Xiao; Zhou, Jing; Qin, Fei; Hou, Lianbing (Planta Medica, 2014)
Postoperative adhesions develop after nearly every abdominal surgery. The formation of adhesions is associated with the inflammatory response, fibrinolytic system, and extracellular matrix deposition in response to injury. Tanshinone IIA is one of the major extracts obtained from Salvia miltiorrhiza, which has anti-inflammatory effects on many diseases. Postoperative adhesions were induced by injuring the parietal peritoneum and cecum in Wistar rats, followed by the administration of various dosages of tanshinone IIA. The adhesion scores for each group were collected seven days after the initial laparotomy. The activity of the tissue-type plasminogen activator in the peritoneal lavage fluid was measured. The messenger ribonucleic acid expression levels of the tissue-type plasminogen activator, plasminogen activator inhibitor-1, and cyclooxygenase-2 in the ischaemic tissues were measured by quantitative real-time polymerase chain reaction. The intraperitoneal administration of tanshinone IIA is effective for the prevention of the formation of postoperative adhesions in rats. Tanshinone IIA increased fibrinolytic activity in the peritoneal lavage fluid and tissue-type plasminogen activator messenger ribonucleic acid expression in ischaemic peritoneal tissues but decreased the plasminogen activator inhibitor and cyclooxygenase-2 messenger ribonucleic acid expression significantly. These results revealed that tanshinone IIA was a potent postoperative adhesion preventer by enhancing fibrinolytic activity and decreasing cyclooxygenase-2 activity.
Keywords: tanshinone IIA; peritoneal adhesions; tPA; PAI-1; inflammatory response; peritoneal fibrinolysis; COX-2